Desain Ballast Water Treatment System Kapal Sesuai Standar IMO - Naufal Adi Hidayah; Eko Julianto; Lely Pramesti (Politeknik Perkapalan Negeri Surabaya, 2023)
The ballast water system are important to maintain ships’s stability during voyage especially when shipnot carrying any cargo. The exchange of ballast water were considered as the main cause of microorganism andbacterias spreading that damaging port water ecosystems. To prevent the damage from harmful microorganism andbacterias on ballast water discharge, in 2004 International Maritime Organization (IMO) established and adoptedBallast Water Management Convention (BWMC). Before complying with IMO BWMC standard, MT GunungGeulis’s existing ballast water system were evaluated and the result says that MT Gunung Geulis are not compatiblewith IMO BWMC standard because still using ballast water exchange method to manage their ballast water. Tocomply with IMO BWMC standard, MT Gunung Geulis need to added ballast water treatment system (BWTS). Basedon journal review to comparing BWTS treatment methods says that filtration + electrolysis method giving the highestefficiency on removing microorganism and bacterias from ballast water. BWTS unit installed on MT Gunung Geulishad three main equipment, filtration unit, electrolysis unit and neutralizer unit from Ocean Guard to be located onturbine and partial deck Filtration unit and electrolysis unit are operated on ballasting process and neutralizationunit injecting neutralizer on deballasting process..